Flowing Gas Experiments Reveal Mechanistic Details of Interfacial Reactions on a Molecular Level at Knudsen Flow Conditions - Iannarelli, Riccardo; Ludwig, Christian; Rossi, Michel J. (Frontiers in Astronomy and Space Sciences, 2022)
The use of Knudsen flow experiments and its interpretation in terms of adsorption/desorption kinetics as well as quantitative uptake on substrates of interest is presented as well as the description of critical design parameters of the Knudsen Flow Reactor (KFR). Hitherto focused almost exclusively on the uptake phase exposing a virgin substrate to interacting gases, we now extend the experiment and its interpretation to the desorption phase at ambient temperature that represents a window of opportunity for the study of heterogeneous reactions. We present analytical expressions for different experimental situations in terms of adsorption (ka), desorption (kd) and effusion (ke) rate constants. The knowledge of kd opens up a new perspective in that surface residence times (1/kd) may now be studied under the same experimental conditions as the uptake (ka) which leads to the determination of the Langmuir equilibrium constant KL = ka/kd for a specific probe gas-condensed phase substrate pair. We emphasize the interaction of semivolatile organic probe gases and small polar molecules with amorphous carbon and mineral dust materials at ambient temperatures as well as a scheme to characterize the molecular interface in terms of a reactivity map of the interface using up to ten different probe gases in an effective titration technique leading to saturation of the uptake of each probe gas. Several examples are used to underline the broad applicability of the technique such as the characterization of the silver/air (Ag) interface as well as the reactivity of TiO2 materials towards uptake of CO2 and CH3OH exploring the properties of these substrates as adsorbents or catalytic materials. In addition, following characterization of several types of amorphous carbon a model incorporating several structural elements in agreement with the reactive gas titration is proposed. As an example, an interface that is at the time weakly basic and strongly reducing is composed of pyrones and hydroquinones whose simultaneous occurrence leads to stable free radicals (environmentally persistent free radicals). Moreover, the question is raised what makes a substrate surface such as PAC or mineral dust materials hydrophobic in terms of surface functional groups when interacting with small polar molecules such.......